2020
DOI: 10.1097/mao.0000000000002632
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cervical and Ocular Vestibular Evoked Myogenic Potential Testing Using an Impulse Hammer in Adults, Adolescents, and Children

Abstract: Objective: To characterize cervical and ocular vestibular evoked myogenic potential (c- and oVEMP) responses using an impulse hammer (IH) in adults and pediatrics at standardized force levels and evaluate: the relationship of force level on VEMP amplitude, sternocleidomastoid (SCM) contraction on cVEMP amplitude, required number of tap stimuli, and subject comfort. Using these data, optimal testing parameters were selected. Study Design: Prospective stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Caution therefore should be exercised when extending findings for high frequency BCV and ACS from small rodents to humans. Given human utricular morphology and the inertia of the head, clinically relevant short-duration stimuli (e.g., mechanical tap ( 58 , 59 )) likely evoke synchronized neural responses that scale with linear acceleration rather than jerk ( Figure 9 , left).…”
Section: Discussionmentioning
confidence: 99%
“…Caution therefore should be exercised when extending findings for high frequency BCV and ACS from small rodents to humans. Given human utricular morphology and the inertia of the head, clinically relevant short-duration stimuli (e.g., mechanical tap ( 58 , 59 )) likely evoke synchronized neural responses that scale with linear acceleration rather than jerk ( Figure 9 , left).…”
Section: Discussionmentioning
confidence: 99%
“…Taps were administered at a bandage used as a target to reduce variability. The data collection program provided simultaneous feedback on appropriate rate and to ensure that only taps between 10 and 30 N were accepted for analysis (Rodriguez et al 2020). The epoch began when the hammer force exceeded a 2.0 N threshold.…”
Section: Methodsmentioning
confidence: 99%
“…The epoch began when the hammer force exceeded a 2.0 N threshold. There is a ~1 ms delay (Rodriguez et al 2020); thus, all IH latencies were adjusted accordingly in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This equals the force output of the B81 when the frequency is 500 Hz ( 16 , 17 , 28 ). We believe that forehead stimulation may be the best location for the oVEMP response instead of the mastoid ( 17 , 28 , 32 ). Our results showed that the response rate of B81-oVEMP was 100% up to the age group of 40–49 years and progressively declined afterward to only 40% in the group of individuals ≥60 years.…”
Section: Discussionmentioning
confidence: 99%